TGF-β induced chemoresistance in liver cancer is modulated by xenobiotic nuclear receptor PXR. Issue 24 (17th December 2019) - Bhagyaraj, Ella; Ahuja, Nancy; Kumar, Sumit; Tiwari, Drishti; Gupta, Shalini; Nanduri, Ravikanth; Gupta, Pawan
ABSTRACT: Hepatocellular carcinoma appears as an extremely angiogenic solid tumor marked by apoptosis evasion, dysregulated cell cycle and low sensitivity to chemotherapy. TGF-β, a multifunctional cytokine, plays a pleiotropic role in the tumor microenvironment and has implications in cancer drug resistance. The current study provides novel evidence that TGF-β signaling contributes to drug resistance in liver cancer cells by inducing the expression of xenobiotic nuclear receptor PXR. We observed that PXR increases the expression of drug efflux transporters; therefore, accounting for exacerbated drug resistance. Additionally, anti-apoptotic nature of PXR contributes to TGF-β mediated chemoresistance as seen by procaspase-3 and Mcl-1 cellular levels. TGF-β binding to the TGF-β receptor triggers a complex downstream signaling cascade through a non-canonical SMAD-independent ERK pathway that leads to increased PXR expression. Activated ERK activates ETS1 transcription factor which is a critical regulator of endogenous PXR expression in hepatic cells. Loss of function of ETS1 abrogates the TGF-β induced PXR expression. Together these findings indicate that PXR modulates TGF-β induced resistance to chemotherapy in liver cancer cells. This underscores the need for combinatorial approaches with focus on PXR antagonism to improve drug effectiveness in hepatocellular carcinoma. Abbreviations: HCC: Hepatocellular Carcinoma; FDA: Food and Drug Administration; TGF-β: Transforming growth factor-β; PXR: Pregnane X receptor; CAR: Constitutive androstane receptor; P-gp/ABCB1: P-glycoproteins/ATP-binding cassette transporter subfamily B member 1; MRP1/ABCC1 and MRP2/ABCC2: Multidrug-resistance associated proteins; BCRP/ABCG2: Breast cancer resistant protein; DMEs: Drug-metabolizing enzymes; CFDA: 5, 6-carboxyfluorescein diacetate; ETS1: Transcription factor E26 transformation specific sequence 1.